2009
DOI: 10.1093/chemse/bjp002
|View full text |Cite
|
Sign up to set email alerts
|

A Candidate Pheromone Receptor and Two Odorant Receptors of the Hawkmoth Manduca sexta

Abstract: In this study, we cloned and characterized three Manduca sexta odorant receptors (ORs). One receptor is a putative pheromone receptor expressed exclusively in a cell associated with male-specific type-I trichoid sensilla. We describe the results of real-time PCR (RT-PCR) and quantitative real-time PCR (qRT-PCR) experiments that show MsextaOR1 is expressed only in male antennae. In situ hybridization labels a single cell associated with type-1 trichoid sensilla, which houses two neurons that have been previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 73 publications
3
55
1
Order By: Relevance
“…Because of their high sequence variability, the most common method to identify ORcoding genes is to analyze genomic sequence databases. For Manduca, the coreceptor (MsexOR-2) and five OR-coding genes have been identified (46,47). Transcripts for all except MsexOR-3 were present in our data; MsexOR-2 and MsexOR-6 could also be extended to full-length.…”
Section: Resultsmentioning
confidence: 49%
“…Because of their high sequence variability, the most common method to identify ORcoding genes is to analyze genomic sequence databases. For Manduca, the coreceptor (MsexOR-2) and five OR-coding genes have been identified (46,47). Transcripts for all except MsexOR-3 were present in our data; MsexOR-2 and MsexOR-6 could also be extended to full-length.…”
Section: Resultsmentioning
confidence: 49%
“…Amino acid sequences for ORs identified from B. mori (Wanner et al, 2007) and H. virescens (Krieger et al, 2002(Krieger et al, , 2004 along with odorant receptor members of the pheromone receptor subfamily from Ostrinia nubialis (Wanner et al, 2010), Manduca sexta (Patch et al, 2009), Cydia pomonella (Bengtsson et al, 2012;Garczynski, unpublished), Plutella xylostella (Mitsuno et al, 2008), Mythimna separata (Mitsuno et al, 2008), Diaphania indica (Mitsuno et al, 2008), and A. transitella (this study) were aligned using the Clustal W program (Thompson et al, 1994) built into the MEGA5 software. The bootstrap consensus tree was inferred from 500 replicates (Felsenstein, 1985) and branches corresponding to partitions reproduced in less than 50% bootstrap replicates are collapsed.…”
Section: Classification Of the Atraor4 Receptorsmentioning
confidence: 99%
“…Subsequently, members of this subfamily have been referred to as male-biased sex pheromone receptor clade (Jordan et al, 2009), sex pheromone receptor subfamily (Miura et al, 2009(Miura et al, , 2010Wanner et al, 2010), pheromone receptors (Patch et al, 2009;Große-Wilde et al, 2010), and male-specific OR subfamily (Mitsuno et al, 2008). To gain a better understanding of how lepidopteran sex pheromones work at the molecular level, research to identify and characterize pheromone receptors in males has been the topic of much research (Krieger et al, 2004(Krieger et al, , 2005Sakurai et al, 2004;Nakagawa et al, 2005;Große-Wilde et al, 2007Wanner et al, 2007Wanner et al, , 2010Mitsuno et al, 2008;Jordan et al, 2009;Miura et al, 2009Miura et al, , 2010Patch et al, 2009;Xu et al, 2012). However, some members of the pheromone receptor subfamily are also activated by plant kairomones (Jordan et al, 2009;Bengtsson et al, 2014), indicating that not all of these ORs respond to pheromones.…”
Section: Introductionmentioning
confidence: 99%
“…Another potential target for cAMP, which might increase SP amplitude, could be the ubiquitous OR83b analogue MsextaOR2 (Patch et al, 2009;Wicher et al, 2008). It remains to be investigated whether MsextaOR2 is cAMP sensitive and involved in pheromone transduction of M. sexta.…”
Section: Potential Antennal Targets Of Campmentioning
confidence: 99%
“…Same lower case letters denote no significant differences between tested groups of mean values. cAMP affects ORNs time dependently Furthermore, 8bcAMP might affect the spontaneous activity via direct or indirect interaction with the putative cAMP-sensitive OR83b analogue MsextaOR2 (Patch et al, 2009;Wicher et al, 2008), because olfactory sensilla lacking OR83b receptors showed very little or no spontaneous AP activity (Larsson et al, 2004). However, the physiological relevance of the observed changes in the spontaneous AP frequency remains to be determined.…”
Section: Effects On the Spontaneous Ap Frequencymentioning
confidence: 99%